(untitled) (Bulletin of the International Association for Paleodontology, 2021)
In the transition period from the Early Iron Age to the Middle Ages, the disintegration of the centralized early state Sargat community and the formation of new cultures are observed on the territory of Western Siberia. The main goal of this study was to find a possible links between Early Medieval and Early Iron Age populations of Western Siberia forest-steppe zone using dental non-metric traits. The frequencies of thirty traits were observed using ASUDAS (and A.A. Zubov’s program). The study was based on the dental remains of 49 individuals from four Great Migration period burial grounds (Ustyug-1, Kozlov Mis, Revda-5, Ipkul) located in Tobol River region of Western Siberia. For comparison were observed 424 individuals of Sargat culture from the burial sites located in the area between the Tobol, Irtysh, and Ishim rivers including the Baraba forest-steppe zone of Western Siberia. Trigonometrically transformed dental trait frequencies were subjected to the principal component analysis. Besides Sargat culture samples, 32 Early Iron Age dental samples from different region of Eurasia were used for statistical comparison. As a result, it was established the Sargat population (especially from Tobol river region and Baraba forest-steppe zone) became a basis for the formation of the Early Medieval tribes of Lower Tobol river region. ‘Eastern’ complex of dental traits were almost absent there except for the shoveling of upper medial incisors and the deflecting wrinkle on the lower first molars.